Heritage, semiotics and innovations: architectural space, object-designs, meanings and implications in sustainable development - Saidi, Umali (Taylor & Francis (Routledge), 2019)
When matters of sustainable development and innovation are on the table for discussion in Africa, culture is often sidelined. Designs, shapes and sizes of new technological innovations need to integrate African aesthetes as a way to uphold the culture of people represented who often utilize or benefit from the inventions or constructions. Artefactual materials or objects (such as buildings) should appeal to the people of Africa and solve their daily challenges. Using semiotics, this paper cautions innovators, planners, thinkers and producers of “modern” residential homes; that these, as material objects, have other roles they play. Dwellings assume the heritage of a people far removed from the traditionally thought spaces and objects such as drums, museums, songs, literary texts, pieces of cloth and so on. As such, planners have a mandate to deliberately uphold their people’s cultural sensitivity if sustainable development is to mean in Zimbabwe and Africa in general.